Lev S. Vygotsky's cultural-historical theory and Soviet psychology of religion: did they overlap? - Alexey Dvoinin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The paper examines the role played by one of the basic Marxist psychological theories in developing Soviet psychology of religion. An attempt is made to find out whether the cultural-historical theory of Lev S. Vygotsky overlapped with this field of knowledge. The author reconstructs a general picture of the objective relationship between cultural-historical theory and Soviet psychology of religion. The nature of this relationship has been identified in four key dimensions: the problems studied, research methodology, academic communities, and academic institutions. The first two dimensions relate to the cognitive aspect of science, the last two – to the social aspect. It is noted that Lev S. Vygotsky’s research did not touch on specific issues of the psychology of religion. The exception is his reference to the problem of magical thinking. Other cultural-historical theorists also did not focus on religious issues. Only a few rare examples of religious life can be found in their works. At the same time, it is argued that the works of cultural-historical theorists were cited by Soviet researchers of religion. However, neither the conceptual ideas of Lev S. Vygotsky (i.e., semiotic mediation, lower and higher mental functions, stages of children’s mental development and age-related new mental structures, etc.) nor his methodological innovations were ever systematically applied and elaborated in Soviet psychology of religion. The paper also finds no trace of an overlap between cultural-historical theory and Soviet psychology of religion in academic communities and institutions, except for the participation of Lev S. Vygotsky and Alexander R. Luria in the discussion of Lucien Lévi-Bruhl’s theory of prelogical thinking, which took place in the 1924-1930s. The article offers explanations for the research results described. Presumably, it was the formation of a negative attitude of science towards religion in the Soviet period under the political and ideological influences that made the meaningful overlap between Lev S. Vygotsky’s cultural-historical theory and the Soviet psychology of religion problematic.